Keberadaan Hakim Komisaris dan Transparansi dalam Proses Penyidikan (the existence of judge commissioner And the transparency of the process of investigation) - Muhaimin Muhaimin (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2016)
Criminal Procedure Code in the document asserted that the defendant-formation-convict defendant as a